Epiphysial dysplasia: a constant finding in the XXXXY syndrome. Issue 4 (August 1978) - Schmidt, R; Pajewski, M; Rosenblatt, M
Abstract : Two patients with the XXXXY syndrome are presented. Both boys are mentally retarded with short stature, muscular hypotonia, and hypogonadism. A constant feature of this syndrome is a varying degree of epiphysial dysplasia probably secondary to hypotonia and growth deceleration.